WORKSHOP PEMBUATAN GAME EDUKASI BERBASIS UNITY UNTUK SISWA SEKOLAH MENENGAH ATAS: UNITY-BASED EDUCATIONAL GAME MAKING WORKSHOP FOR HIGH SCHOOL STUDENTS (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
AbstractTextbooks are standard learning media commonly used by educators and students in the teaching-learning process. However, it has limitations in terms of flexibility and visual appeal. Along with the development of digital technology and the increasing use of smartphones among teenagers, a more interactive and attractive learning media is needed. To answer this need, a workshop on making Unity-based educational games was conducted for students and teachers at SMA Negeri 2 Manado. This activity was carried out through three main stages, namely counseling, direct training/workshop on the use of Unity, and monitoring the results of activities for three months. The results of this activity showed an increase in participants' interest and understanding of the concept of educational game development. The resulting application has main features in the form of learning materials, evaluation questions, and an English-based mini dictionary. This activity also strengthens collaboration between universities and secondary schools in developing learning innovations. Thus, Unity-based educational game development training can be an effective solution to improve student motivation and learning outcomes..